Exploring the bacterial diversity and its antibiotic resistance in Kabru Glacier ice cores, Sikkim Himalaya - Tamang, Sonia; Sherpa, Mingma Thundu; Kumar, Santosh; Najar, Ishfaq Nabi; Sharma, Prayatna; Das, Sayak; Jiya, Namrata; Sharma, Avinash; Pandey, Piyush; Thakur, Nagendra (Frontiers in Microbiology, 2026)
IntroductionThe Kabru Glacier, located in the Sikkim Himalayan region at an altitude of 7,318–7,412 m above sea level (a.s.l), forms part of the Kanchenjunga range in the Eastern Himalaya. Glaciers in this region are predominantly summer-fed and highly sensitive to climatic fluctuations. Despite their ecological significance, glaciers of the Sikkim Himalaya remain largely unexplored from a microbiological perspective due to harsh weather conditions and limited accessibility. In this context, the present study investigates the bacterial diversity across different depths (upper, middle, and bottom) of ice core samples collected from the Kabru Glacier.MethodsBacterial diversity was examined using a combination of culture-dependent and culture-independent approaches. In addition, antibiotic resistance profiles and metal tolerance characteristics of the isolated bacteria were evaluated to gain further insight into their adaptive potential.Results and discussionCulture-dependent analysis revealed a comparatively high bacterial load in the Kabru Glacier, suggesting that the biodiversity-rich Himalayan surroundings may influence the microbial community structure. Phenotypic characterization showed a predominance of Gram-positive bacteria (62.6%) over Gram-negative bacteria (37.3%). Growth profile analyses indicated optimal growth temperatures of 15°C and 20°C, with variable tolerance to salinity and pH, reflecting adaptive responses to environmental stress. Elemental analysis of ice core samples revealed higher concentrations (ppb range) of Na, Mg, K, Ca, Mn, Li, and Zn compared to other elements. Phylogenetic analysis based on 16S rRNA gene sequencing identified members of the phyla Pseudomonadota, Bacillota, and Actinomycetota. Consistently, culture-independent 16S rRNA amplicon sequencing also demonstrated the dominance of these phyla. Alpha diversity indices corroborated trends observed in the culture-dependent analysis, supporting the complementary reliability of both methodologies in elucidating bacterial community structure. Furthermore, antibiotic susceptibility testing revealed resistance to cefixime (CFM) and metronidazole (MET), along with elevated tolerance to heavy metals such as CuSO4, ZnCl2, and NiCl2, while showing lower tolerance to HgCl2.ConclusionCollectively, these findings suggest that bacterial diversity in the Kabru Glacier is shaped by multiple environmental parameters. The occurrence of antibiotic-resistant and metal-tolerant bacteria underscores the need for further comprehensive investigations to better understand microbial adaptation and potential ecological implications in high-altitude glacial ecosystems.